Effect of work material and machining conditions on the accuracy and quality of micro holes. (3rd April 2009) - Mathew, Jose; Somashekhar, K.P.; Sooraj, V.S.; Subbarao, Nuvvula; , N. Ramachandran
This paper presents the analysis on accuracy and surface quality of micro holes produced by micro-electric discharge machining (μ-EDM). Preliminary investigations reveal that appropriate selections of process parameters and work material were very much essential for efficient cutting. The overcut of the produced micro holes was analysed through experimentation and SEM analysis during the first phase of the study. A regression model was developed using the surface response methodology. During the second phase of the work, the effect of work materials on the accuracy and efficiency of μ-EDM drilling was analysed. With discharge energy of 500 μJ, minimum overcut of 35 μm was observed in aluminium plate, whereas in the die steel and stainless steel, it was 9 μm. The melting point of the material was identified as the significant factor deciding the accuracy and surface quality of micro holes. A regression model was also developed to predict the erosion efficiency and it was validated with experimental data.